Process for preparing titanium-tungsten powder by deep purification of waste de-nitrification catalyst and carrier reconstruction

CN122979629APending Publication Date: 2026-10-27SHANGHAI SHIDONGKOU NO 2 POWER PLANT HUANENG INTERNATIONAL POWER CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610962313.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,对于机械结构破损严重、烧结、中毒程度深而无法再生的废催化剂,只能采用回收路线,即通过湿法冶金或火法冶金工艺提取其中的有价金属

Benefits of technology

[0017]本公开提出一种废脱硝催化剂深度净化与载体重构制钛钨粉工艺,本公开具有以下优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979629A_ABST
    Figure CN122979629A_ABST
Patent Text Reader

Abstract

The present disclosure provides a waste denitration catalyst deep purification and carrier reconstruction titanium tungsten powder preparation process, comprising: waste denitration catalyst classification, crushing, grinding and screening; waste denitration catalyst mechanical ash removal, washing, solid-liquid separation to obtain solid material; the solid material is made into slurry and complexing agent and penetrant are added for ultrasonic chemical combined cleaning, solid-liquid separation to obtain first filter cake; the first filter cake is added to the alkaline cleaning solution to prepare the slurry, heat preservation reaction, solid-liquid separation and washing to obtain the second filter cake; the second filter cake is added to the protonic acid solution to prepare the slurry heat preservation reaction, the reducing agent is added to adjust the solution stirring reaction, solid-liquid separation to obtain the crude titanium tungsten carrier; the crude titanium tungsten carrier is prepared into slurry and is activated, crystallized, reconstructed and surface modified; the slurry is filtered, dewatered, beaten, washed, dried and superfine crushed to obtain fine titanium tungsten intermediate powder; the magnetic iron impurities and light impurities are removed, and the fine titanium tungsten powder is obtained by crushing; the fine titanium tungsten powder is quality detected, graded and packaged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of industrial solid waste resource utilization technology, specifically involving a process for deep purification of waste denitrification catalyst and carrier reconstruction to produce titanium tungsten powder. Background Technology

[0002] Selective catalytic reduction (SCR) denitrification technology is currently the most widely used technology in industrial flue gas denitrification fields such as coal-fired power plants, steel plants, and cement plants. Its core component is a vanadium-titanium-tungsten (vanadium-titanium-tungsten) denitrification catalyst. This type of catalyst typically uses titanium dioxide as a carrier, vanadium pentoxide as the main active component, and tungsten trioxide as a co-catalyst. In actual operation, the catalyst gradually deactivates due to poisoning by alkali metals (K, Na), alkaline earth metals (Ca, Mg), and heavy metals (As, Pb, Hg) in the flue gas, as well as fly ash abrasion, sintering, and pore blockage. Its service life is generally 3-5 years. With the rapid development of my country's denitrification industry, the amount of waste denitrification catalysts generated annually exceeds one million tons and is showing a year-on-year increasing trend.

[0003] Waste denitrification catalysts are classified as hazardous waste, containing heavy metals such as vanadium and tungsten, as well as unreacted toxic substances. Improper disposal or dumping can cause serious pollution to soil, water, and the atmosphere. However, waste denitrification catalysts also contain large amounts of valuable metals such as titanium, tungsten, and vanadium, with titanium dioxide content approximately 80%-85%, tungsten trioxide content approximately 5%-10%, and vanadium pentoxide content approximately 1%-5%, giving them extremely high resource utilization value.

[0004] Currently, the resource utilization of spent denitrification catalysts mainly falls into two categories: regeneration and recycling. Catalyst regeneration refers to restoring the catalyst's activity through methods such as physical cleaning, chemical cleaning, and replenishment of active components. This method is suitable for spent catalysts with intact mechanical structures and mild poisoning. However, for spent catalysts with severely damaged mechanical structures, sintering, or deep poisoning that cannot be regenerated, only the recycling route can be adopted, i.e., extracting valuable metals through hydrometallurgical or pyrometallurgical processes.

[0005] Traditional hydrometallurgical recycling processes mainly include acid leaching, alkali leaching, and roasting-leaching, which have the following problems: First, impurities are not completely removed, especially toxic impurities such as alkali metals and arsenic, which are difficult to remove deeply, resulting in low-quality recovered titanium-tungsten powder that cannot be directly used to prepare new denitrification catalysts; second, vanadium-tungsten separation is poor, with a high tungsten loss rate and low resource utilization; third, the recovered titanium-tungsten powder has problems such as collapsed pore structure, small specific surface area, and few active sites, which lead to low initial catalyst activity and rapid degradation when directly used to prepare new catalysts; fourth, the process is complex, energy-intensive, and causes serious secondary pollution, making it difficult to achieve large-scale industrial application. Summary of the Invention

[0006] This disclosure aims to at least solve one of the technical problems existing in the prior art, and to provide a process for deep purification of waste denitrification catalysts and reconstruction of carriers to produce titanium-tungsten powder.

[0007] This disclosure provides a process for deep purification and carrier reconstruction of waste denitrification catalysts to produce titanium-tungsten powder, the process comprising: S110. Collect, classify, crush, coarsely grind, and screen the waste denitrification catalyst. S120. Mechanically remove ash, wash, and separate solid and liquid materials from the waste denitrification catalyst after screening to obtain solid materials. S130. The solid material is made into a slurry, and a complexing agent and a penetrant are added. The mixture is then subjected to ultrasonic and chemical combined cleaning, followed by solid-liquid separation to obtain the first filter cake. S140. The first filter cake is added to an alkaline cleaning solution to prepare a slurry, which undergoes a first heat preservation reaction, followed by solid-liquid separation and washing to obtain a second filter cake. S150. The second filter cake is added to a protic acid solution to prepare a slurry. After a second heat preservation reaction, a reducing agent is added to adjust the pH value of the solution and the reaction is stirred to precipitate vanadium ions. Solid-liquid separation is then performed to obtain a crude titanium-tungsten carrier. S160. The crude titanium-tungsten carrier is prepared into a slurry and then subjected to activation treatment, crystal reconstruction and surface modification in sequence. S170. The reconstructed slurry is filtered and dehydrated, repeatedly pulped and washed, dried and ultra-finely pulverized to obtain fine titanium-tungsten intermediate powder. S180. Remove magnetic iron impurities and light impurities from the fine titanium-tungsten intermediate powder, and perform secondary pulverization to obtain fine titanium-tungsten powder. S190. The fine titanium tungsten powder is subjected to quality testing, and graded and packaged according to the test results.

[0008] Optionally, in step S110, the particle size of the waste denitrification catalyst after crushing and coarse grinding is no greater than 2 mm.

[0009] Optionally, in step S120, the screened waste denitrification catalyst is fed into an air classifier, and fly ash and loose agglomerated impurities are separated by high-speed airflow generated by compressed air, with the airflow velocity controlled at 15-20 m / s. The catalyst particles after mechanical ash removal are sent to a high-pressure water cleaning device. The surface of the catalyst particles is washed with high-pressure water jet. The washing pressure is controlled at 15-25MPa and the washing time is 10-20min. The material after high-pressure water cleaning is sent into a centrifuge for solid-liquid separation. The centrifuge speed is controlled at 2500-3500 r / min, and the separation time is 3-7 min.

[0010] Optionally, in step S130, the solid-liquid ratio of the solid material to the water in the slurry is 1:(3-5); The complexing agent is ethylenediaminetetraacetic acid or citric acid, and its addition amount is 2%-4% of the mass of the waste denitrification catalyst. The penetrant is sodium dodecylbenzenesulfonate or polyethylene glycol, and its content is 0.5%-1.2% of the mass of the spent denitrification catalyst. The power of the combined ultrasonic and chemical cleaning is controlled at 450-550W / L, the stirring speed is controlled at 250-350r / min, and the cleaning time is 50-70min.

[0011] Optionally, in step S140, the solid-liquid ratio of the filter cake in the slurry to the alkaline cleaning solution is 1:(4-6); The temperature of the first heat preservation reaction is 60-80℃, and the heat preservation reaction time is 90-120min.

[0012] Optionally, in step S150, the solid-liquid ratio of the second filter cake to the protic acid solution in the slurry is 1:(3-5); The temperature of the second heat preservation reaction is 80-90℃, and the heat preservation reaction time is 150-180 min; The reducing agent is sodium sulfite or oxalic acid, and its addition amount is 1.2-2.0 times the vanadium content in the waste denitrification catalyst; Adjust the pH of the solution to 2.5-3.0.

[0013] Optionally, in step S160, the solid-liquid ratio of the coarse titanium-tungsten carrier to water in the slurry is 1:(3-5).

[0014] Optionally, in step S160, the slurry undergoes activation treatment, crystal reconstruction, and surface modification sequentially, including: An activator is added to the slurry, and the reaction is carried out at 80-90℃ for 60-90 minutes to activate the titanium-tungsten support. Add a crystal form regulator to the activated slurry, adjust the pH of the solution to 7.5-8.5, and continue the reaction at a constant temperature for 120-150 minutes to allow the titanium-tungsten support to undergo crystallization reconstruction. Add a surface modifier to the slurry after crystallization and reconstruction, and stir for 50-70 minutes to modify the surface of the titanium-tungsten support.

[0015] Optionally, the activator is hydrogen peroxide or ammonium persulfate, and its addition amount is 3%-5% of the mass of the crude titanium-tungsten carrier; The crystal form regulator is tetrabutyl titanate or isopropyl titanate, and its addition amount is 1%-2.5% of the mass of the crude titanium-tungsten carrier; The surface modifier is a silane coupling agent, and its addition amount is 0.5%-1% of the mass of the crude titanium-tungsten carrier.

[0016] Optionally, in step S170, the drying temperature is 120-150℃ and the drying time is 10-20 min, so that the moisture content of the material is reduced to below 1%; The particle size D90 of the ultrafine pulverized titanium-tungsten intermediate powder is no greater than 10 μm.

[0017] This disclosure proposes a process for deep purification of spent denitrification catalysts and carrier reconstruction to produce titanium-tungsten powder, which has the following advantages: 1. Achieve high efficiency and stability in the reconstruction of waste denitrification catalyst supports through a carrier surface-bulk phase coupling reconstruction process; 2. By using acid leaching to remove impurities and vanadium-tungsten cascade separation technology, impurities are effectively removed and vanadium-tungsten resources are recycled. 3. Through a multi-stage purification process combining electromagnetic iron removal and gravity screening, magnetic iron impurities and light silicon and aluminum impurities are precisely removed. 4. By implementing a quality inspection, graded packaging, and non-conforming product recycling mechanism for titanium tungsten powder, we ensure the stability of product quality. Attached Figure Description

[0018] Figure 1 This is a flowchart illustrating the process for deep purification of waste denitrification catalyst and carrier reconstruction to produce titanium-tungsten powder, which is a specific embodiment of this disclosure. Detailed Implementation

[0019] To enable those skilled in the art to better understand the technical solutions of this disclosure, the disclosure will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this disclosure and represent a part of the embodiments of this disclosure, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without creative effort are within the protection scope of this disclosure.

[0020] like Figure 1 As shown, one aspect of this disclosure provides a process for deep purification of waste denitrification catalysts and carrier reconstruction to produce titanium-tungsten powder, characterized in that the process includes: S110. Waste catalyst pretreatment: Waste denitrification catalyst is collected, classified, crushed, coarsely ground, and screened.

[0021] Step S110 includes the following specific processes: Waste catalyst collection and classification: Waste denitrification catalysts from different industrial sources are collected and classified according to their source, service life, degree of poisoning and damage. Waste catalysts with severe mechanical damage, sintering and non-renewable are selected as raw materials.

[0022] Crushing and coarse grinding: The waste catalyst is fed into a jaw crusher for primary crushing until the particle size is no more than 50 mm. Then it is fed into a hammer crusher for secondary crushing until the particle size is no more than 10 mm. Finally, it is fed into a ball mill for coarse grinding until the particle size is no more than 2 mm.

[0023] Screening: The coarsely ground material is fed into a vibrating screen for screening. The material on the screen is returned to the ball mill for further grinding, and the material under the screen is collected.

[0024] S120 Mechanical ash removal and high-pressure water cleaning: The waste denitrification catalyst after screening is mechanically ash removed, rinsed, and separated into solid and liquid materials to obtain solid materials.

[0025] Step S120 includes the following specific processes: Mechanical ash removal: The screened waste catalyst powder is fed into an air classifier, which uses high-speed airflow generated by compressed air to separate fly ash and loose agglomerated impurities. The airflow velocity is controlled at 15-20m / s, and the catalyst particles are collected.

[0026] High-pressure water cleaning: The catalyst particles are sent into a high-pressure water cleaning device, and the surface of the catalyst particles is rinsed with high-pressure water jet. The rinsing pressure is controlled at 15-25MPa and the rinsing time is 10-20min.

[0027] Solid-liquid separation: The rinsed material is sent to a centrifuge for solid-liquid separation. The centrifuge speed is controlled at 2500-3500 r / min and the separation time is 3-7 min. The separated wastewater is treated and reused, and the separated solid material is collected for later use.

[0028] S130, Ultrasonic and chemical combined cleaning: The solid material is made into a slurry, and a complexing agent and a penetrant are added. Ultrasonic and chemical combined cleaning is performed, followed by solid-liquid separation to obtain the first filter cake.

[0029] Step S130 includes the following specific processes: Pulping: The solid material obtained from S120 is fed into the reactor, pure water is added to prepare a slurry with a solid-liquid ratio of 1:3-1:5, and the mixture is stirred evenly.

[0030] Ultrasonic chemical cleaning: Add complexing agent and penetrant to the slurry, turn on the ultrasonic generator and stirring device, and carry out ultrasonic chemical cleaning.

[0031] In the above steps, the complexing agent is ethylenediaminetetraacetic acid or citric acid, and its addition amount is 2%-4% of the mass of the waste denitrification catalyst.

[0032] In the above steps, the penetrant is sodium dodecylbenzenesulfonate or polyethylene glycol, and its content is 0.5%-1.2% of the mass of the waste denitrification catalyst.

[0033] In the above steps, the power of the combined ultrasonic and chemical cleaning is controlled at 450-550W / L, the stirring speed is controlled at 250-350r / min, and the cleaning time is 50-70min.

[0034] Solid-liquid separation: The washed slurry is fed into a plate and frame filter press for solid-liquid separation. The separated filtrate is treated and reused, and the first filter cake is collected.

[0035] S140, Alkaline medium deep arsenic removal: The first filter cake is added to an alkaline cleaning solution to prepare a slurry, which undergoes a first heat preservation reaction, followed by solid-liquid separation and washing to obtain a second filter cake.

[0036] Step S140 includes the following specific processes: Preparation of alkaline medium: Prepare an alkaline cleaning solution based on the arsenic content in the waste catalyst.

[0037] Alkaline arsenic removal reaction: The first filter cake obtained from S130 is sent into the reactor, and an alkaline cleaning solution is added to prepare a slurry with a solid-liquid ratio of 1:4-1:6. After stirring evenly, the temperature is raised to the reaction temperature for the first heat preservation reaction.

[0038] In the above steps, the temperature of the first heat preservation reaction is 60-80℃, and the heat preservation reaction time is 90-120min.

[0039] Solid-liquid separation: The reacted slurry is fed into a plate and frame filter press for solid-liquid separation. The separated filtrate is sent to the arsenic recovery system. The filter cake is washed with pure water until neutral and collected for later use.

[0040] S150, Acid leaching for impurity removal and vanadium-tungsten stepwise separation: The second filter cake is added to a protic acid solution to prepare a slurry. After a second heat preservation reaction, a reducing agent is added to adjust the pH value of the solution and the reaction is stirred to precipitate vanadium ions. Solid-liquid separation is then performed to obtain crude titanium-tungsten support.

[0041] Step S150 includes the following specific processes: Preparation of acid leaching solution: Prepare a protic acid solution as the acid leaching solution.

[0042] Acid leaching reaction: The second filter cake obtained from S140 is sent into the reactor, and acid leaching solution is added to prepare a slurry with a solid-liquid ratio of 1:3-1:5. After stirring evenly, the temperature is raised to the reaction temperature to carry out the second heat preservation reaction.

[0043] In the above steps, the temperature of the second heat preservation reaction is 80-90℃, and the heat preservation reaction time is 150-180min.

[0044] Vanadium-tungsten cascade separation: A reducing agent is added to the acid-leached slurry, the pH value of the solution is adjusted to the set range, and the reaction is stirred to cause vanadium ions to precipitate.

[0045] In the above steps, the reducing agent is sodium sulfite or oxalic acid, and the amount added is 1.2-2.0 times the vanadium content in the waste denitrification catalyst.

[0046] In the above steps, the pH of the solution is adjusted to 2.5-3.0.

[0047] Solid-liquid separation: The slurry after reaction is sent to a plate and frame filter press for solid-liquid separation. The separated filter cake is a crude titanium-tungsten carrier, and the separated filtrate is sent to a vanadium recovery system. Tungsten ions remain in the solution and are subsequently recovered by crystallization.

[0048] S160, Carrier Surface-Bulk Coupling Reconstruction: The crude titanium-tungsten carrier is prepared into a slurry and then subjected to activation treatment, crystallization reconstruction and surface modification in sequence.

[0049] Step S160 includes the following specific processes: Carrier activation: The crude titanium-tungsten carrier obtained by S150 is sent into the reactor, pure water is added to prepare a slurry with a solid-liquid ratio of 1:3-1:5, after stirring evenly, an activator is added, the temperature is raised to the reaction temperature, and the reaction is kept at the temperature for activation treatment.

[0050] In the above steps, the activation reaction temperature is 80-90℃ and the time is 60-90min.

[0051] In the above steps, the activator is hydrogen peroxide or ammonium persulfate, and its addition amount is 3%-5% of the mass of the crude titanium-tungsten carrier.

[0052] Crystallization reconstruction: Add crystal form regulator to the activated slurry, adjust the pH value of the solution to the set range, and continue the reaction at a constant temperature to carry out crystallization reconstruction, so that the titanium-tungsten support undergoes crystallization reconstruction and restores its pore structure and specific surface area.

[0053] In the above steps, adjust the pH of the solution to 7.5-8.5 and continue the reaction at this temperature for 120-150 minutes.

[0054] In the above steps, the crystal form regulator is tetrabutyl titanate or isopropyl titanate, and its addition amount is 1%-2.5% of the mass of the crude titanium-tungsten carrier.

[0055] Surface modification: A surface modifier is added to the slurry after crystallization reconstruction, and the mixture is stirred and reacted for a certain period of time to modify the surface of the titanium-tungsten support, thereby improving its surface properties and the distribution of active sites.

[0056] In the above steps, the stirring reaction time is 50-70 minutes.

[0057] In the above steps, the surface modifier is a silane coupling agent (e.g., KH550), and its addition amount is 0.5%-1% of the mass of the crude titanium-tungsten support.

[0058] S170, Filtration, Washing and Drying: The reconstructed slurry is filtered and dehydrated, repeatedly pulped and washed, dried and ultra-finely pulverized to obtain fine titanium-tungsten intermediate powder.

[0059] Step S170 includes the following specific processes: Filtration and washing: The slurry obtained from S160 is sent to a diaphragm press for filtration and dewatering to obtain a filter cake. The filter cake is then repeatedly slurried and washed with pure water until the conductivity of the washing liquid is lower than the set value.

[0060] Drying: The washed filter cake is sent to a flash dryer for drying, so that the moisture content of the material is reduced to below 1%.

[0061] In the above steps, the drying temperature is 120-150℃ and the drying time is 10-20 minutes, so that the moisture content of the material is reduced to below 1%.

[0062] Crushing: The dried material is fed into an air jet mill for ultrafine crushing.

[0063] In the above steps, the particle size D90 of the ultrafine titanium-tungsten intermediate powder after ultrafine grinding is no greater than 10 μm.

[0064] S180, Electromagnetic iron removal and gravity screening: Remove magnetic iron impurities and light impurities from the fine titanium tungsten intermediate powder, and perform secondary crushing to obtain fine titanium tungsten powder.

[0065] Step S180 includes the following specific processes: Electromagnetic iron removal: The crushed material is fed into an electromagnetic iron separator to remove solid magnetic iron impurities.

[0066] Gravity screening: The material after electromagnetic iron removal is sent to a gravity separator to remove light impurities such as silicon and aluminum.

[0067] Secondary crushing: The material after gravity screening is fed back into the air jet mill for further crushing.

[0068] S190. Quality Inspection and Grading Packaging of Titanium Tungsten Powder: The fine titanium tungsten powder is subjected to quality inspection, and graded and packaged according to the inspection results.

[0069] Step S190 includes the following specific processes: Quality inspection: The prepared titanium-tungsten powder is tested for chemical composition, physical properties and microstructure; the test items include potassium content, sodium content, arsenic content, iron content, aluminum content, silicon content, specific surface area, pore volume, pore size distribution, crystal structure, etc.

[0070] Graded Packaging: Titanium tungsten powder is graded according to the test results. Titanium tungsten powder that meets the requirements is packaged with moisture-proof and oxidation-proof packaging materials and stored in the warehouse; titanium tungsten powder that does not meet the requirements is returned to the process system for reprocessing.

[0071] The process disclosed herein can not only deeply remove toxic and harmful impurities from waste denitrification catalysts, but also achieve efficient separation of vanadium and tungsten and reconstruction of the titanium-tungsten support structure, producing high-quality titanium-tungsten powder that meets the requirements for high-proportion addition to prepare new denitrification catalysts.

[0072] The following will further illustrate the process of deep purification of spent denitrification catalysts and carrier reconstruction to produce titanium-tungsten powder with specific embodiments: Example 1 S110, Pretreatment of spent catalyst Step S110 specifically includes: collecting spent SCR denitrification catalyst from a 600MW coal-fired power plant. This catalyst has been in use for four years, with severe mechanical damage and sintering in some parts, making it impossible to restore its activity through regeneration. The spent catalyst is fed into a jaw crusher for primary crushing, reducing the particle size to no more than 50mm. It is then fed into a hammer crusher for secondary crushing, reducing the particle size to no more than 10mm. Finally, it is fed into a ball mill for coarse grinding, reducing the particle size to no more than 2mm. The coarsely ground material is then fed into a vibrating screen for sieving, with a screen aperture of 2mm. The material exceeding the screen size is returned to the ball mill for further grinding, while the material passing through the screen is collected for later use.

[0073] S120, Mechanical dust removal and high-pressure water cleaning Step S120 specifically includes: feeding the sieved waste catalyst powder into an air classifier, using high-speed airflow generated by compressed air to separate fly ash, loose agglomerated impurities from the catalyst particles, with the airflow velocity controlled at 15-20 m / s, and collecting the catalyst particles. The mechanically de-ashed catalyst particles are then fed into a high-pressure water cleaning device, where a high-pressure water jet washes the surface of the catalyst particles, with the washing pressure controlled at 20 MPa and the washing time at 15 min, removing fly ash and soluble impurities adhering to the surface of the catalyst particles. The material after high-pressure water cleaning is then fed into a centrifuge for solid-liquid separation, with the centrifuge speed controlled at 3000 r / min and the separation time at 5 min. The separated wastewater is sent to a wastewater treatment system for treatment and reuse, and the separated solid material is collected for later use.

[0074] S130, combined ultrasonic and chemical impurity removal Step S130 specifically includes: feeding the solid material obtained in S120 into a reaction vessel, adding pure water to prepare a slurry with a solid-liquid ratio of 1:4, and stirring evenly. Adding ethylenediaminetetraacetic acid (EDTA) as a complexing agent to the slurry, the amount added is 2%-3% of the mass of the spent catalyst; adding sodium dodecylbenzenesulfonate as a penetrant, the amount added is 0.5%-1% of the mass of the spent catalyst. Turning on the ultrasonic generator and stirring device, controlling the ultrasonic frequency at 40kHz, the ultrasonic power at 500W / L, and the stirring speed at 300r / min, performing ultrasonic-chemical combined cleaning for 60min. Sending the ultrasonically and chemically cleaned slurry into a plate and frame filter press for solid-liquid separation, controlling the filtration pressure at 0.6MPa, sending the separated filtrate to a wastewater treatment system for treatment and reuse, and collecting the separated filter cake for later use.

[0075] S140, Alkaline Medium Deep Arsenic Removal Step S140 specifically includes: preparing a 5% sodium bicarbonate solution as an alkaline cleaning solution based on the arsenic content in the spent catalyst. The filter cake obtained in S130 is fed into a reaction vessel, and the alkaline cleaning solution is added to prepare a slurry with a solid-liquid ratio of 1:5. After stirring evenly, the mixture is heated to 80°C and kept at this temperature for 120 minutes. The reacted slurry is then fed into a plate and frame filter press for solid-liquid separation, with the filtration pressure controlled at 0.6 MPa. The separated filtrate is sent to an arsenic recovery system to recover arsenic. The separated filter cake is washed with pure water until neutral, and the pH value of the washing solution is monitored during the washing process until it reaches 7-8. The washed cake is then collected for later use.

[0076] S150, acid leaching for impurity removal and vanadium-tungsten cascade separation Step S150 specifically includes: preparing a 2 mol / L sulfuric acid solution as the leaching solution. The filter cake obtained in S140 is fed into a reaction vessel, and the leaching solution is added to prepare a slurry with a solid-liquid ratio of 1:4. After stirring evenly, the mixture is heated to 90°C and kept at this temperature for 180 min. Sodium sulfite is added to the leached slurry as a reducing agent, the amount added being 1.2-1.5 times the vanadium content in the spent catalyst. The pH of the solution is adjusted to 2.5-3.0, and the mixture is stirred for 60 min to reduce vanadium ions to tetravalent vanadium ions and form vanadium hydroxide precipitate, while tungsten ions remain in the solution. The reacted slurry is fed into a plate and frame filter press for solid-liquid separation, with the filtration pressure controlled at 0.6 MPa. The separated filter cake is a crude titanium-tungsten support, which is collected for later use. The separated filtrate is sent to a vanadium recovery system to recover vanadium, while tungsten ions remain in the solution and are subsequently recovered by evaporation crystallization.

[0077] S160, Carrier Surface-Bulk Coupling Reconstruction Step S160 specifically includes: feeding the crude titanium-tungsten support obtained in S150 into a reactor, adding pure water to prepare a slurry with a solid-liquid ratio of 1:4, stirring evenly, adding hydrogen peroxide as an activator at a rate of 3%-5% of the crude titanium-tungsten support mass, heating to 80℃, and holding the reaction at this temperature for 90 min to activate the titanium-tungsten support, oxidizing and removing residual organic impurities and reducing substances from the support surface, while simultaneously generating more hydroxyl groups on the support surface. Tetrabutyl titanate is then added to the activated slurry as a crystal form regulator at a rate of 1%-2% of the crude titanium-tungsten support mass, adjusting the pH of the solution to 8.0-8.5, and continuing the reaction at this temperature for 120 min to cause crystallization reconstruction of the titanium-tungsten support, transforming amorphous titanium dioxide into anatase titanium dioxide, while simultaneously restoring its pore structure and specific surface area. Silane coupling agent KH-550 was added to the slurry after crystallization and reconstruction as a surface modifier. The amount added was 0.5%-1% of the mass of the crude titanium-tungsten support. The mixture was stirred and reacted for 60 min to modify the surface of the titanium-tungsten support, improve its surface properties and distribution of active sites, and enhance its binding ability with active components.

[0078] S170, Filtration, Washing, Drying, and Pulverization Step S170 specifically includes: feeding the slurry obtained in S160 into a diaphragm press for filtration and dewatering, with the pressing pressure controlled at 1.2 MPa, to obtain a filter cake. Then, the filter cake is repeatedly washed with pure water, with a solid-liquid ratio of 1:4 each time, and a stirring time of 30 minutes. The mixture is then filtered, and the washing process is repeated until the conductivity of the washing liquid is below 100 μS / cm. The washed filter cake is then fed into a flash dryer for drying, with the drying temperature controlled at 130℃ and the drying time at 15 minutes, reducing the moisture content of the material to below 1%. The dried material is then fed into an air jet mill for ultrafine grinding, with the grinding pressure controlled at 0.8 MPa, until the particle size D90 is no greater than 10 μm.

[0079] S180, Electromagnetic Iron Removal and Gravity Screening Step S180 specifically includes: feeding the pulverized material into an electromagnetic separator, with the magnetic field strength controlled at 15000 Gs, to remove solid magnetic iron impurities from the material. The material after electromagnetic iron removal is then fed into a gravity separator, with water as the separation medium and a separation speed controlled at 0.5-1.0 m / s, to remove light impurities such as silicon and aluminum. The material after gravity screening is then fed again into an air jet mill for further pulverization to ensure uniform particle size, with a particle size D90 not exceeding 10 μm.

[0080] S190, Titanium Tungsten Powder Quality Inspection and Grading Packaging Step S190 specifically includes: analyzing the chemical composition, physical properties, and microstructure of the prepared titanium-tungsten powder. Chemical composition was analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES), physical properties were analyzed using a specific surface area and pore size analyzer, and microstructure was analyzed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results showed that the titanium-tungsten powder contained 0.008% potassium, 0.006% sodium, 0.003% arsenic, 0.012% iron, 0.021% aluminum, and 0.035% silicon, with a specific surface area of ​​85 m². 2 / g, pore volume 0.32cm 3 The titanium tungsten powder has a density of / g, an average pore size of 15nm, and an anatase crystal form, meeting the requirements for high-quality titanium tungsten powder. The qualified titanium tungsten powder is packaged in aluminum foil composite bags, 25kg per bag, and stored in a warehouse.

[0081] Example 2 This embodiment provides a process for deep purification of waste denitrification catalyst and carrier reconstruction to produce titanium-tungsten powder, which differs from Embodiment 1 in that: In step S140, a 2% sodium hydroxide solution is used as the alkaline cleaning solution, the reaction temperature is 60℃, and the reaction time is 90 min.

[0082] In step S150, a 1.5 mol / L hydrochloric acid solution is used as the leaching solution, the reaction temperature is 80℃, and the reaction time is 150 min.

[0083] In step S160, ammonium persulfate is used as an activator, and the amount added is 4%-6% of the mass of the crude titanium-tungsten carrier. The activation reaction temperature is 90℃ and the holding time is 60min.

[0084] The other steps are the same as in Example 1.

[0085] The prepared titanium-tungsten powder was subjected to quality testing. The results showed that the titanium-tungsten powder contained 0.009% potassium, 0.007% sodium, 0.004% arsenic, 0.015% iron, 0.023% aluminum, and 0.038% silicon, with a specific surface area of ​​82 m². 2 / g, pore volume 0.30cm 3 / g, with an average pore size of 16nm, and an anatase titanium dioxide crystal form, meeting the requirements for high-quality titanium tungsten powder.

[0086] Example 3: This embodiment provides a process for deep purification of waste denitrification catalyst and carrier reconstruction to produce titanium-tungsten powder, which differs from Embodiment 1 in that: In S130, citric acid is used as a complexing agent, with an addition amount of 3%-4% of the mass of the spent catalyst, and polyethylene glycol is used as a permeating agent, with an addition amount of 0.8%-1.2% of the mass of the spent catalyst.

[0087] In step S150, oxalic acid is used as a reducing agent, and the amount added is 1.5-2.0 times the vanadium content in the waste catalyst. The pH value of the solution is adjusted to 2.0-2.5, and the stirring reaction time is 90 min.

[0088] In step S160, isopropyl titanate is used as a crystal form regulator, and the amount added is 1.5%-2.5% of the mass of the crude titanium tungsten support. The pH value of the crystallization reconstruction reaction is 7.5-8.0, and the heat preservation reaction time is 150 min.

[0089] The other steps are the same as in Example 1.

[0090] The prepared titanium-tungsten powder was subjected to quality testing. The results showed that the titanium-tungsten powder contained 0.007% potassium, 0.005% sodium, 0.002% arsenic, 0.010% iron, 0.018% aluminum, and 0.032% silicon, with a specific surface area of ​​88 m². 2 / g, pore volume is 0.34cm 3 / g, with an average pore size of 14nm, and an anatase titanium dioxide crystal form, meeting the requirements for high-quality titanium tungsten powder.

[0091] Comparative Example 1: This comparative example provides a traditional process for recovering spent denitrification catalysts to produce titanium-tungsten powder, including the following steps: S110, waste catalyst is crushed and ball-milled until the particle size is no larger than 200 mesh; S120. Use a 3 mol / L sulfuric acid solution to acid-leach at 100℃ for 4 hours, with a solid-liquid ratio of 1:5. S130, filtration, to obtain acid leaching residue and acid leaching solution; S140, the acid leaching residue is washed with pure water until neutral, and then dried to obtain titanium tungsten powder; S150, an acid leaching solution, is used to recover vanadium and tungsten.

[0092] The prepared titanium-tungsten powder was subjected to quality testing. The results showed that the titanium-tungsten powder contained 0.12% potassium, 0.08% sodium, 0.05% arsenic, 0.15% iron, 0.22% aluminum, and 0.35% silicon, with a specific surface area of ​​35 m². 2 / g, pore volume 0.12cm 3 / g, with an average pore size of 25nm, and a crystal form that is a mixture of anatase and rutile, does not meet the requirements for high-quality titanium tungsten powder.

[0093] Comparative Example 2: This comparative example provides a process for recovering waste denitrification catalyst to produce titanium-tungsten powder, which differs from Example 1 in that: The carrier surface-bulk phase coupling reconstruction step in S160 is omitted; the other steps are the same as in Example 1.

[0094] The prepared titanium-tungsten powder was subjected to quality testing. The results showed that the titanium-tungsten powder contained 0.009% potassium, 0.007% sodium, 0.004% arsenic, 0.013% iron, 0.022% aluminum, and 0.036% silicon, with a specific surface area of ​​42 m². 2 / g, pore volume 0.15cm 3 / g, with an average pore size of 22nm, and a crystal form that is a mixture of anatase and amorphous crystal forms, does not meet the requirements for high-quality titanium tungsten powder.

[0095] Comparative Example 3: This comparative example provides a process for recovering waste denitrification catalyst to produce titanium-tungsten powder, which differs from Example 1 in that: In step S150, vanadium-tungsten cascade separation was not performed; the acid-leached slurry was directly filtered to obtain a titanium-tungsten carrier.

[0096] The prepared titanium-tungsten powder was subjected to quality testing. The results showed that the titanium-tungsten powder contained 0.008% potassium, 0.006% sodium, 0.003% arsenic, 0.012% iron, 0.021% aluminum, 0.035% silicon, and 0.85% vanadium, with a specific surface area of ​​83 m². 2 / g, pore volume is 0.31cm 3 The titanium dioxide has an average pore size of 15 nm and is anatase-type. Although the impurity content and specific surface area meet the requirements, the excessive vanadium content will lead to unstable activity of the subsequently prepared new catalyst and reduced vanadium recovery rate.

[0097] In summary, based on the results of Examples 1-3, the titanium-tungsten powder obtained using the process of this embodiment has extremely low impurities and a specific surface area of ​​82-88 m². 2 / g, pore volume 0.30-0.34cm 3 / g, etc., all indicators met the standards. However, in Comparative Example 1, using a traditional process without multi-stage impurity removal, vanadium-stage separation, or carrier reconstruction, the alkali metal, arsenic, and iron impurities in the titanium-tungsten powder severely exceeded the standards, and the titanium-tungsten powder crystal form contained rutile, with a specific surface area of ​​only 35m². 2 / g, with extremely low pore volume, the product is unqualified; Comparative Example 2, after omitting the S160 carrier coupling and reconstruction process, produces titanium-tungsten powder with an amorphous phase and a specific surface area of ​​only 42m². 2 / g, the pore volume decreased significantly and still did not meet the requirements of the catalyst support. This indicates that the surface-bulk phase coupling reconstruction of the support is the key core step that determines the pores, specific surface area and crystal form of titanium tungsten. After the vanadium step-separation of Comparative Example 3 (omitting step S150), the arsenic / alkali metal / iron impurities, specific surface area and crystal form are qualified, but the vanadium content of the titanium tungsten powder is 0.85%. Excessive vanadium residue in titanium tungsten powder will cause the new catalyst to run out of control and the vanadium resources cannot be recovered separately.

[0098] This disclosure proposes a process for deep purification of spent denitrification catalysts and reconstruction of the support to produce titanium-tungsten powder, which has the following advantages compared to existing technologies: First, this invention utilizes a combined ultrasonic and chemical impurity removal technology. By leveraging the cavitation effect of ultrasound and the complexation effect of chemical reagents, it effectively removes soluble iron, aluminum, and alkali metal impurities such as potassium and sodium from spent catalysts. This method achieves high removal efficiency with minimal structural damage to the titanium-tungsten support. Second, through a deep arsenic removal technology using alkaline media, different concentrations and types of alkaline cleaning solutions can be employed to select appropriate arsenic removal conditions based on the arsenic content and its form in the spent catalyst, achieving deep arsenic removal while minimizing tungsten loss.

[0099] Secondly, this invention utilizes acid leaching for impurity removal and vanadium-tungsten staged separation technology. By using a protic acid solution for acid leaching, residual impurities in the waste catalyst can be effectively removed. At the same time, by adding a reducing agent to adjust the pH value of the solution, vanadium ions are selectively precipitated, while tungsten ions remain in the solution, achieving efficient separation of vanadium and tungsten with a high vanadium recovery rate and a low tungsten loss rate.

[0100] Third, this invention utilizes a carrier surface-bulk phase coupling reconstruction technology. An activator is used to activate the titanium-tungsten carrier, removing residual impurities from the carrier surface and increasing surface hydroxyl groups. Then, a crystal form regulator is added to induce crystal reconstruction in the titanium-tungsten carrier, restoring its anatase crystal form and pore structure, thereby increasing its specific surface area and pore volume. Finally, a surface modifier is added to modify the surface of the titanium-tungsten carrier, improving its surface properties and active site distribution, and enhancing its binding ability with active components.

[0101] It is understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of this disclosure, and this disclosure is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and substance of this disclosure, and these modifications and improvements are also considered to be within the scope of protection of this disclosure.

Claims

1. A process for deep purification of waste denitrification catalyst and carrier reconstruction to produce titanium-tungsten powder, characterized in that, The process includes: S110. Collect, classify, crush, coarsely grind, and screen the waste denitrification catalyst. S120. Mechanically remove ash, wash, and separate solid and liquid materials from the waste denitrification catalyst after screening to obtain solid materials. S130. The solid material is made into a slurry, and a complexing agent and a penetrant are added. The mixture is then subjected to ultrasonic and chemical combined cleaning, followed by solid-liquid separation to obtain the first filter cake. S140. The first filter cake is added to an alkaline cleaning solution to prepare a slurry, which undergoes a first heat preservation reaction, followed by solid-liquid separation and washing to obtain a second filter cake. S150. The second filter cake is added to a protic acid solution to prepare a slurry. After a second heat preservation reaction, a reducing agent is added to adjust the pH value of the solution and the reaction is stirred to precipitate vanadium ions. Solid-liquid separation is then performed to obtain a crude titanium-tungsten carrier. S160. The crude titanium-tungsten carrier is prepared into a slurry and then subjected to activation treatment, crystal reconstruction and surface modification in sequence. S170. The reconstructed slurry is filtered and dehydrated, repeatedly pulped and washed, dried and ultra-finely pulverized to obtain fine titanium-tungsten intermediate powder. S180. Remove magnetic iron impurities and light impurities from the fine titanium-tungsten intermediate powder, and perform secondary pulverization to obtain fine titanium-tungsten powder. S190. The fine titanium tungsten powder is subjected to quality testing, and graded and packaged according to the test results.

2. The process according to claim 1, characterized in that, In step S110, the particle size of the waste denitrification catalyst after crushing and coarse grinding is no greater than 2 mm.

3. The process according to claim 1, characterized in that, In step S120, the screened waste denitrification catalyst is fed into an air classifier, where high-speed airflow generated by compressed air separates fly ash and loose agglomerated impurities, with the airflow velocity controlled at 15-20 m / s. The catalyst particles after mechanical ash removal are sent to a high-pressure water cleaning device. The surface of the catalyst particles is washed with high-pressure water jet. The washing pressure is controlled at 15-25MPa and the washing time is 10-20min. The material after high-pressure water cleaning is sent into a centrifuge for solid-liquid separation. The centrifuge speed is controlled at 2500-3500 r / min, and the separation time is 3-7 min.

4. The process according to claim 1, characterized in that, In step S130, the solid-liquid ratio of the solid material to water in the slurry is 1:(3-5); The complexing agent is ethylenediaminetetraacetic acid or citric acid, and its addition amount is 2%-4% of the mass of the waste denitrification catalyst. The penetrant is sodium dodecylbenzenesulfonate or polyethylene glycol, and its content is 0.5%-1.2% of the mass of the spent denitrification catalyst. The power of the combined ultrasonic and chemical cleaning is controlled at 450-550W / L, the stirring speed is controlled at 250-350r / min, and the cleaning time is 50-70min.

5. The process according to claim 1, characterized in that, In step S140, the solid-liquid ratio of the first filter cake in the slurry to the alkaline cleaning solution is 1:(4-6); The temperature of the first heat preservation reaction is 60-80℃, and the heat preservation reaction time is 90-120min.

6. The process according to claim 1, characterized in that, In step S150, the solid-liquid ratio of the second filter cake to the protic acid solution in the slurry is 1:(3-5); The temperature of the second heat preservation reaction is 80-90℃, and the heat preservation reaction time is 150-180 min; The reducing agent is sodium sulfite or oxalic acid, and its addition amount is 1.2-2.0 times the vanadium content in the waste denitrification catalyst; Adjust the pH of the solution to 2.5-3.

0.

7. The process according to claim 1, characterized in that, In step S160, the solid-liquid ratio of the crude titanium-tungsten carrier to water in the slurry is 1:(3-5).

8. The process according to claim 1, characterized in that, In step S160, the slurry undergoes activation treatment, crystal reconstruction, and surface modification in sequence, including: An activator is added to the slurry, and the reaction is carried out at 80-90℃ for 60-90 minutes to activate the titanium-tungsten support. Add a crystal form regulator to the activated slurry, adjust the pH of the solution to 7.5-8.5, and continue the reaction at a constant temperature for 120-150 minutes to allow the titanium-tungsten support to undergo crystallization reconstruction. A surface modifier was added to the slurry after crystallization and reconstruction, and the reaction was stirred for 50-70 minutes to modify the surface of the titanium-tungsten support.

9. The process according to claim 8, characterized in that, The activator is hydrogen peroxide or ammonium persulfate, and its addition amount is 3%-5% of the mass of the crude titanium-tungsten carrier. The crystal form regulator is tetrabutyl titanate or isopropyl titanate, and its addition amount is 1%-2.5% of the mass of the crude titanium-tungsten carrier; The surface modifier is a silane coupling agent, and its addition amount is 0.5%-1% of the mass of the crude titanium-tungsten carrier.

10. The process according to claim 1, characterized in that, In step S170, The drying temperature is 120-150℃, and the drying time is 10-20 minutes, so that the moisture content of the material is reduced to below 1%. The particle size D90 of the ultrafine pulverized titanium-tungsten intermediate powder is no greater than 10 μm.